Automated Brain Extraction from T2-weighted Magnetic Resonance Images - Datta, Sushmita (2011)
PURPOSE: To develop and implement an automated and robust technique to extract brain from T2-weighted images. MATERIALS AND METHODS: Magnetic resonance imaging (MRI) was performed on 75 adult volunteers to acquire dual fast spin echo (FSE) images with fat-saturation technique on a 3T Philips scanner. Histogram-derived thresholds were derived directly from the original images followed by the application of regional labeling, regional connectivity, and mathematical morphological operations to extract brain from axial late-echo FSE (T2-weighted) images. The proposed technique was evaluated subjectively by an expert and quantitatively using Bland-Altman plot and Jaccard and Dice similarity measures. RESULTS: Excellent agreement between the extracted brain volumes with the proposed technique and manual stripping by an expert was observed based on Bland-Altman plot and also as assessed by high similarity indices (Jaccard: 0.9825± 0.0045; Dice: 0.9912 ±0.0023). CONCLUSION: Brain extraction using proposed automated methodology is robust and the results are reproducible.